Dermatopathology Clinicopathological Correlations - Cockerell, Clay. (Springer London : Imprint: Springer, 2014)
With significant progress as new techniques to evaluate the pathology of the skin, this book satisfies the need to provide practical clinical information and concise criteria for pathologic diagnosis for pathologists and dermatologists looking for an up-to-date resource. This superb visual reference provides detailed instruction of the experience of both diagnostic pathology and clinical dermatology. Dermatopathology: Clinicopathological Correlations is a comprehensive but concise visual reference that contains specific features on the various clinical findings and histologic findings of skin diseases. It emphasizes criteria for diagnosis to help the trainee pathologist or dermatologist decipher the most important features and make clinical decisions quickly and effectively.